Quo Vadis Hadith Studies in Islamic Boarding Schools in Al-Jabiri's Perspective - Anam, Wahidul; Sulaeman, Mubaidi; Mustakim, Andi Ardiyan; Putra, Afriadi; Hakim, Lukmanul (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2024)
This study aims to analyze the paradigm shift and the direction of the hadith study objectives at Ma'had Aly HasyimAs-sari Jombang used the perspective of Muhammad Abid Al-Jabiriy's Arabic reasoning. This study used a descriptive curative approach. Technical Data Analysis Using Miles and Huberman Theory with three steps: data collection, data reduction, third data presentation, verification, and data conclusions. Primary and secondary data were used in this study. Secondary data were obtained from secondary sources, such as tabloids, magazines, bulletins, and online opinions, while primary data were obtained from primary sources, such as interviews and observations. This study found that first, the Islamic Boarding School, especially Ma'had Aly Hasyim Asaraiy, in essence has long used irfani and bayani reasoning in the form of hadith studies as a counter to the extreme burhani reasoning of Western civilization as a counterweight. However, lately, Islamic boarding school education with its Ma'had Aly begin to be carried away by the strandarization of such education. Second, Ma'had Aly education has a purpose as a response to global changes in the world of education which requires formality as an authority for recognizing the knowledge of its graduates, but has a big consequence that one day the boarding school will lose its irfanical reasoning characteristics by sinking into extreme burhani reasoning in the national education system implemented by the government.